1994
DOI: 10.1540/jsmr.30.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastrectomy on Motility, Perfusion Pressure, and Caerulein-Induced Relaxation of Sphincter of Oddi in Dogs.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…31 This paradoxical response is also observed in patients with gastrectomy, and in conscious dogs with proximal duodenal transection. 9,12,13 Our present study has found, for the first time, that the paradoxical response is not mediated by CCK receptors on the SO smooth muscle, but may be mediated by a mechanism requiring SOduodenal myoneural continuity.…”
Section: Discussionsupporting
confidence: 46%
“…31 This paradoxical response is also observed in patients with gastrectomy, and in conscious dogs with proximal duodenal transection. 9,12,13 Our present study has found, for the first time, that the paradoxical response is not mediated by CCK receptors on the SO smooth muscle, but may be mediated by a mechanism requiring SOduodenal myoneural continuity.…”
Section: Discussionsupporting
confidence: 46%
“…However, at present, there are few studies on the effect of Gabexate mesilate on the SO. Research by Kobayashi et al [15] on Gabexate mesilate's inhibitory effect on the SO in dogs was realized by non-adrenergic and noncholinergic passageway. Di Francesco et al [16] adopted the endoscope manometry to study Gabexate mesilate's effect on the SO.…”
Section: Discussionmentioning
confidence: 99%
“…21 The inhibitory effect of cerulein, an analogue of CCK, on the canine SO reverses to excitation after gastrectomy. 24 Although CCK has a direct excitatory effect on gut smooth muscle, there is another inhibitory pathway, only in the SO. [38][39][40] Our recent experiment showed that CCK exhibited a "paradoxical" response, contraction instead of relaxation, after proximal duodenal transection and anastomosis in conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, the effect of CCK on the SO becomes excitatory after distal gastrectomy in humans. 23,24 Moreover, it was also reported that translocation of the papilla to the jejunum 25 changed SO motility. Our recent study also showed that duodenal transection and anastomosis 1 cm distal to the pylorus reduced the SO basal pressure and reversed the SO response to CCK, from inhibition to stimulation and from reduction of the basal pressure to elevation.…”
Section: Introductionmentioning
confidence: 97%